Nab-paclitaxel-associated photosensitivity: report in a woman with non-small cell lung cancer and review of taxane-related photodermatoses - Bryce D. Beutler; Philip R. Cohen (Mattioli1885, 2015)
Background: Taxanes [paclitaxel, nab-paclitaxel (Abraxane, Celgene Corp, USA), and docetaxel]-used in the treatment of lung, breast, and head and neck cancers-have been associated with cutaneous adverse effects, including photodermatoses. Purpose: We describe a woman with non-small cell lung cancer who developed a photodistributed dermatitis associated with her nab-paclitaxel therapy and review photodermatoses in patients receiving taxanes. Materials and methods: The features of a woman with a nab-paclitaxel-associated photodistributed dermatitis are presented and the literature on nab-paclitaxel-associated photosensitivity is reviewed. Results: Our patient developed nab-paclitaxel-associated photodistributed dermatitis on the sun-exposed surfaces of her upper extremities, which was exacerbated with each course of nab-paclitaxel. Biopsies revealed an interface dermatitis and laboratory studies were negative for lupus erythematosus and dermatomyositis. Her condition improved following topical corticosteroid cream application and strict avoidance of sunlight. Conclusion: Chemotherapy can be associated with adverse mucocutaneous events, including dermatoses on sun-exposed areas of the skin. Paclitaxel and nab-paclitaxel have both been associated with photodermatoses, including dermatitis, erythema multiforme, onycholysis, and subacute cutaneous lupus erythematosus. Strict avoidance of sun exposure, topical or oral corticosteroids, and/or discontinuation of the drug results in improvement with progressive resolution of symptoms and skin lesions. Development of photodermatoses is not an absolute contraindication to continuing chemotherapy, provided that the cutaneous condition resolves with dermatosis-directed treatment and the patient avoids sun exposure.